Association of HER2 overexpression and prognosis in small (T1N0) primary breast cancers - Rom, Joachim; Schumacher, Claudia; Gluz, Oleg; Höfler, Josef; Eidt, Sebastian; Domschke, Christoph; Marmé, Frederik; Nitz, Ulrike; Sohn, Christof; Schneeweiss, Andreas (Breast care, 2013)
Background: There is some controversy regarding the precise role and need for adjuvant therapy in patients with pT1a/pT1bN0 breast cancer, although studies have indicated that a HER2-positive status is one of the most powerful poor prognostic factors. Patients and Methods: We retrospectively evaluated disease-free survival (DFS), distant disease-free survival (DDFS), and overall survival (OS) among 960 patients diagnosed between 2000 and 2008 with T1N0 primary breast cancer treated at 3 German centers, and determined prognostic risk factors. Univariate analysis was used to determine associations with potential risk factors. Results: With a median follow-up of 23 months, DFS was 94.8%, DDFS 96.3%, and OS 97.5%. Risk factors for decreased 1-year DFS were: peritumoral lymphatic invasion (L1) (p = 0.031), negative hormone receptor status (p = 0.003), non-use of hormonal therapy (p = 0.001), and a positive HER2 status (p = 0.003). Amongst the HER2-positive patients only 2.7% (n = 1/37) of those treated with trastuzumab had a DFS event compared with 20% (n = 10/50) without trastuzumab. Conclusion: Patients with HER2-positive T1 breast cancer should be considered for inclusion in prospective trials of trastuzumab in combination with chemotherapy to determine the risk-to-benefit ratio and association with other prognostic factors.